Benefits and restrictions of 2D reactive transport simulations of CO2 and SO2 co-injection into a saline aquifer using TOUGHREACT V3.0-OMP. (November 2016) - Wolf, Jan Lennard; Niemi, Auli; Bensabat, Jacob; Rebscher, Dorothee
Abstract : Highlights: Simulation of reactive transport of CO2 and SO2 injection into a saline aquifer. Novel approach for trace gas transport using TOUGHREACT V3. Importance of ionic strength for numerical results of the simulations. Abstract: Many simulation studies on CO2 storage in deep saline aquifers focus on flow transport modelling and pressure development. Studies including geochemical aspects mostly address the acidic impact of pure CO2 injection on the minerals of the reservoir complex. More recent reactive transport simulations respect compositions of a flue gas stream closer to reality, i.e. they include physical or geochemical impacts of impurities within the CO2 stream. Here the common approach is to introduce trace gases into the multidimensional system as dissolved solutes in an additional aquatic phase, injected into the reservoir as brine. The most recent release of version V3.0-OMP of the TOUGHREACT code provides the new feature "Transport of trace gas species in CO2 –H2 O carrier gas", allowing for direct injection and transport of trace gases in the CO2 phase. This study addresses the geochemical impact of co-injected SO2 as a CO2 flue gas impurity on the reservoir rock in a generic model, based on parameters of the Heletz saline aquifer. Therefore numerical 2D reactive transport simulations applying the trace gas transport approach as provided by TOUGHREACT V3.0 are performed for a ten year injection period. The simulations predict a distinct inner region of 200 m radial distance under the dominating impact of dissolved SO2, while a distance of up to 2000 m is influenced by CO2 . The region impacted by SO2 is characterised by a distinct ankerite dissolution and coupled precipitation pattern of anhydrite. In the analysis of the results, special emphasis is given to the benefits and restrictions of the trace gas transport approach in comparison to the impurity modelling by injection of additional brine, particularly addressing the topic of ionic strength limitations.